Dual-path coupled-line microwave bandpass filter topology for wideband applications / Siti Aminah Nordin - Nordin, Siti Aminah (2014)
This thesis describes the development of a new topology of coupled line bandpass filter for wideband applications. The concept deals with an even number of identical quarter-wavelength coupled lines that are interconnected to form two parallel paths of series-connected coupled lines. Such way, a bandpass response of order | + 1 is resulted, where n is the number of identical coupled lines used. The existence transmission zero at both sides of the passband constitutes the main advantage of this filter topology, where very good selectivity can be ensured, while wide bandwidth can be achieved. The global synthesis of the proposed topology is presented for the case of second order response. The design synthesis was developed to control the electrical characteristics of the resonator such as bandwidth and also to fix the position of the transmission zeros frequencies. Besides, the fractional bandwidth on the in-band matching level can be controlled by varying the value of characteristic impedances of the coupled lines. For implementation of the second-order filter, the uses of symmetrical and asymmetrical coupled lines are studied in order to obtain better performance. In practice, asymmetrical coupled lines are more flexible in obtaining higher wave coupling, for better in-band matching level. A further combination of identical quarter-wavelength coupled lines in the initial second order topology is proposed for higher order design. The topology of second-order and higher order filters are implemented on microstrip technology using two substrates which are FR-4 and TRF45. Simulations and measurement results are presented to validate the idea.